Overconfidence and Health Insurance Participation among the Elderly - Wei Huang; Mi Luo (Institute for the Study of Labor (IZA), 2015)
People may have imperfect information about their health status and thus make suboptimal decisions in insurance participation. Using national representative samples of the elderly in US and China, we find that people with lower socio-economic status and poorer health are relatively less likely to realize how unhealthy they are and this overconfidence is associated with no insurance participation. Accurate health information provided through physical examinations induces relatively higher participation among the overconfident people afterwards. These findings contribute a new explanation for the insufficient participation and advantageous selection in health insurance, and provide new insights on the insurance market and policy suggestions.
Keywords: I12; I13; J14; 330; overconfidence; health; health insurance participation